MISSING LINK KOTA DEPOK (CASE STUDY: MANAGEMENT MISSING LINK AT KOTA DEPOK) - Jalil, Muksin (ASTONJADRO, 2021)
In connection with the important role of the road network and connectivity of public transport in the area of the City of Depok, there is a problem called the missing link. The purpose of this study is reviewed from the aspects of road network performance, connectivity of activity centers, TOD areas and transportation nodes, then obtained by loading the Origin Destination Matrix (MAT) to the road network with the help of transportation modeling software using Saturn. Travel speed between cities/regencies in Jabodetabek or the origin destination of Depok City does not reach the target speed of 40 km/hour, and speeds between regions and within regencies/cities in Depok city. Tangerang Regency and Bekasi Regency have the lowest speeds, with the lowest values being 25.06 km/hour and 25.39 km/hour. So that the need to increase the capacity of the road network to and from Tangerang and Bekasi districts, for Depok city the average speed that occurs within the city is 28.81 km our, so it is necessary to increase the capacity of the road network. The TOD area will have a missing link if the TOD has no connectivity with the mass transit node at a distance of more than 800 meters and is not on the main high-capacity mass transit line, such as the Cinere TOD. The need for handling the missing link TOD area of the road network in the Greater Jakarta area, mainly Cinere - Fatmawati Station. And there is 1 PKN that is not connected by public transportation to other PKN and is not connected with PKW in the same City, namely Cimanggis District, Depok City.